Optimierung von Expositionstherapie bei pathologischen Krankheitsängsten: Theoretische Grundlagen und praktische Implikationen - Gropalis, Maria; Bailer, Josef (Psychotherapeut, 2018)
Up to now pathological health anxiety has been classified primarily as a somatoform disorder or a somatic symptom disorder in ICD and DSM. Theoretical and empirical evidence, however, suggest that pathological health anxiety basically represents an anxiety disorder. In this paper, it is argued that deficits in the treatment and perception of patients with pathological health anxiety as “difficult patients” are partly attributable to a lack of clarity in terms of nosology and with respect to central mechanisms of etiology and pathogenesis. Based on novel theoretical approaches for the explanation of pathological health anxiety, suggestions for an improved therapeutic practice are outlined. This approach focuses on a more intensive use of exposure-based treatment elements that are oriented to the inhibitory learning approach, which has already proven its effectiveness for other anxiety disorders.